2009
DOI: 10.1111/j.1740-0929.2009.00652.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunolocalization of lingual antimicrobial peptide (LAP) in the bovine mammary gland

Abstract: Lingual antimicrobial peptide (LAP), a member of the beta-defensin family in cows, is involved in the innate immune system and plays a crucial role in killing a large variety of microorganisms. The aim of the present study was to demonstrate the immunolocalization of LAP in the mammary glands of cows. A LAP antibody was raised in a rabbit by immunity with a synthetic 11 amino acid sequence out of a 42-amino acid sequence of the mature form of LAP. The specificity of the LAP antibody was checked using a competi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 17 publications
1
52
0
Order By: Relevance
“…Immunohistochemical studies demonstrated the expression of LAP peptide in healthy (Isobe et al . 2009b) and E. coli ‐inoculated mammary epithelial cells (Petzl et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…Immunohistochemical studies demonstrated the expression of LAP peptide in healthy (Isobe et al . 2009b) and E. coli ‐inoculated mammary epithelial cells (Petzl et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we developed LAP antibody using rabbits for immunohistochemical studies. The results demonstrated the expression of LAP peptide in the epithelial cells of alveoli and milk ducts of healthy mammary glands (Isobe et al 2009a; Fig. 1).…”
Section: B-defensinmentioning
confidence: 74%
“…The results demonstrated the expression of LAP peptide in the epithelial cells of alveoli and milk ducts of healthy mammary glands (Isobe et al . ; Fig. ).…”
Section: β‐Defensinmentioning
confidence: 93%
“…Concentrations of S100A7 and S100A8 were determined by enzyme immunoassay (EIA) as described previously (Isobe, Hosoda, & Yoshimura, 2009;Zhang, Lai, Yoshimura, & Isobe, 2014). Antibodies against synthetic S100A7 and S100A8 peptides consisting of 14 and 11 amino acids (CFEKQDKNKDRKID and CLEAHEIHKE), respectively, were raised in rabbits.…”
Section: Measurement Of S100a7 and S100a8mentioning
confidence: 99%